The Growing Phenomenon of Street Children in Tehran: An Empirical Analysis (UKH Journal of Social Sciences, 2019)
This study examines the increasing phenomenon of street children in Tehran. It focuses on the challenges and risks these children encounter and the overall implications on the general populace and the country as a whole. The study adopted both primary and secondary sources of data. The primary data were qualitative design (face-to-face interview). The population include all street children in Tehran. Purposive and snowball sampling techniques were used to select a total of 3725 street children for this research. Information gathered was coded, categorized and analyzed using EZ Test Software to quantify the results and demonstrate the frequency of responses to the open-ended questions relating to the research interest. The study found that there are two categories of street children in Tehran (children of the street and children on the street), they experience several challenges such as extortion, exploitation, rape, and harassment. Furthermore, they engage in different activities to get money or survive. The study concludes that disrupted socioeconomic structure of families and the influx of different categories of people into the cities are the major causes of the phenomenon. The study, therefore, recommends that addressing the socioeconomic challenges should be the first approach toward ending the menace.